Students’ performance in the G.C.E (O/L) examination in the post-war context in the Northern Province of Sri Lanka - Nithlavarnan, A. (University of Colombo, Sri Lanka, 2019)
The Northern Province (NP) of Sri Lanka was affected by the protracted civil war for more than three decades. Before the civil war, NP was leading in the general examinations performance. But in the post war period, performance of students in general examinations has not shown an improvement, especially in the G.C.E (O/L) examination. This study analyses the G.C.E (O/L) examination results of NP with other provinces in Sri Lanka in the pre and post-war context. Secondary data is obtained from statistics reports published by the Department of Examination, Sri Lanka. Descriptive statistics and graphs were used to analyze the data. The study revealed that, in the pre-war era, the percentage of students who passed the G.C.E (O/L) examination in the Northern Province was higher than the national level, while in the post war era it has been reversed. Further, it was found that the percentages of those who passed the G.C.E (O/L) examination within the Northern Province during 2010- 2018 shows an inconsistency between the periods and places. There is a significant difference between National figures and the figures from districts of Jaffna and Kilinochchi during the period. However there is a fluctuation in the difference between National figures and the figures from Mannar and Vavuniya districts during the period. The trend of the G.C.E (O/L) performance during 2010-2018 among the national level and Mullaithivu district implies that Mullaithivu is far below than National performance during the period. When compared with zonal and educational division level, NP is far behind in this context. This study would hopefully benefit academics, researchers, policy-makers and practitioners through exploring the students’ performance in the G.C.E (O/L) examination, and pursing strategies to improve the current status of it.
Keywords: G.C.E (O/L); Northern Province; Performance; Post-war context; School students